2016
DOI: 10.7717/peerj.2666
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity hinders axonal development of motor neurons inCaenorhabditis elegans

Abstract: As space flight becomes more accessible in the future, humans will be exposed to gravity conditions other than our 1G environment on Earth. Our bodies and physiology, however, are adapted for life at 1G gravity. Altering gravity can have profound effects on the body, particularly the development of muscles, but the reasons and biology behind gravity’s effect are not fully known. We asked whether increasing gravity had effects on the development of motor neurons that innervate and control muscle, a relatively u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…Previously, we showed that hypergravity exposure increases DD/VD motor neuron axon defects 22 . Here, we sought to explain how gravity force can alter the axon development in the worm.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Previously, we showed that hypergravity exposure increases DD/VD motor neuron axon defects 22 . Here, we sought to explain how gravity force can alter the axon development in the worm.…”
Section: Resultsmentioning
confidence: 98%
“…Hypergravity cultivation chamber was prepared as previously described 22 . For hypergravity experiment, eggs were collected from gravid adult animals by bleaching using standard procedures 25 and then transferred into the cultivation tube around 100–150 in number.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nematode hypergravity cultivation tub was prepared according to previous protocols 51 . The 1 ml of NGM was placed into each 1.5 ml centrifuge tube and then transferred to a heat block set to prevent immediate solidification of agar.…”
Section: Methodsmentioning
confidence: 99%